Management of chickpea wilt with fungicides - and B.M. SINGH, S.K. SUGHA, S.K. KAPOOR (Indian Phytopathology, 2002)
Twelve fungicides were evaluated against Fusarium oxysporum f. sp. ciceri, which causes chickpea wilt under in vitro, glasshouse and field conditions. Carbendazim (50 WP and 25 DS) and thiram alone and in combination were found highly effective in inhibiting in vitro mycelial growth of the pathogen and in reducing wilt incidence both under glasshouse and field conditions.